Isolation and application of a lactic acid bacterium from Pennisetum Giganteum to improve the silage quality of king grass (Bangladesh Journal of Botany, 2025)
In this study, a dominant strain of Lactiplantibacillus plantarum was isolated from Pennisetum giganteum and used alone or in combination with cellulase, xylanase, and glucose oxidase in a silage experiment with King grass. The results showed that all additives improved the aroma, color, and texture of the silage, as well as enhanced its nutritional content and fermentation quality. Comprehensive analysis indicated that the combination of L. plantarum and xylanase was the most effective, significantly increasing lactic acid content, reducing pH and ammonia nitrogen levels, and improving overall silage quality. This combination shows strong potential for application and provides theoretical and technical support for the utilization of King grass as feed.Bangladesh J. Bot. 54(3): 731-739, 2025 (September) Special